The Implicated Subject in Four South African Autobiographical Texts - Englund, Lena (Journal of southern African studies, 2022)
Finding new ways to address oppressive pasts has been a prominent theme in South African nonfiction since the end of apartheid, writers often seeking to explore personal and collective implication and guilt. The legacies of oppression and discrimination spill over into the South African present of social and economic inequality. This article examines four autobiographical texts that address notions of personal and collective implication in South Africa's apartheid past and its present-day inequality. At the centre of the analysis are Rian Malan's My Traitor's Heart from the end of the apartheid era, which offers a personal exploration of Afrikaner history in South Africa, and Christopher Hope's The Café de Move-on Blues, which attempts to determine the role of English-speaking white South Africans. In addition, Sisonke Msimang writes about class divides and implication crossing racial borders in Always Another Country, and Haji Mohamed Dawjee offers a forceful critique of seemingly well-meaning, guilt-ridden whiteness in Sorry, Not Sorry. The article draws on Michael Rothberg's theorisation of the implicated subject as beneficiary of oppressive pasts beyond simple distinctions of victim and perpetrator. All four texts portray a South Africa in which boundaries are increasingly blurred, and implication transgresses temporal, spatial and racial lines.